PELATIHAN DESIGN PERKANDANGAN SAPI PERAH MELALUI APLIKASI GOOGLE SKETCHUP DI KALANGAN MAHASISWA PETERNAKAN UNIVERSITAS PADJADJARAN - Raden Febrianto Christi; Didin Supriat Tasripin; Eka Wulandari (UNIVERSITAS KHAIRUN, 2022)
The stalls is a place to live for livestock that can provide comfort. A good stalls has a good construction or design. The purpose of this service is to provide information and apply it to students on how to design a stalls for dairy cows through the Google SketchUp application. This activity uses extension methods through online media about the design of a stalls for modern dairy cows, the construction of a stalls that includes a roof, walls and floors, and the types of dairy cowsheds. The provision of material and practice is carried out for one day outside of working hours. The number of participants who took part in this activity was 70 student participants consisting of various generations at the Faculty of Animal Husbandry, Universitas Padjadjaran. The results showed that there was an increase in knowledge and practice among students regarding the design of a dairy cow housing through the Google Sketchup application, namely 100%, which was previously only 30%. Students after going through a series of activities are expected to be able to increase their knowledge and apply the dairy cow housing design through the Googlesketcup application in the world of work.Keywords: training, housing design, dairy cows, googlesketchup, students